Letter from Lieut. Com'dr J. D. Marvin to James Curtis Booth, May 14, 1872 - Marvin, J. D. (1872)
Lieutenant Commander J. D. Marvin follows up with James Curtis Booth (1810-1888) from his letter of February 18 about the use of silver or copper in ordinance experiments at DuPont’s Powder Mill. Marvin apologizes to Booth for the extra work and confirms that silver disks from the Mint work best for the Powder Mill.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; E.I. du Pont de Nemours & Company; Marvin, J. D.